Морфогенез и биосфероцентрическая парадигма жизни В.И. Вернадского - Малецкий, С.И. (Фактори експериментальної еволюції організмів, 2014)
Aims. Briefly describe the views of V.I. Vernadsky on the nature of the living which allowed him to of ideas which can be denoted as “biosferocentrics paradigm” (BSP) of life. Methods. BSP to re-evaluate the role of atoms in the implementation of biochemical functions considering the basic properties of organic molecules should be viewed through the symmetry at the atomic level. The impact of life processes on the symmetry of the atoms can extend to any organic molecules that are the main factor manifestations of life. Results. Within BSP can formulate a general idea of morphogenetic processes as a continuous process of self-implemented under the influence of external forces. Conclusions. Vernadsky to realize the natural diversity of life can not through molecular levels. He wrote: “Now that the biogeochemistry specifically, research has put on the agenda the relationship of life not only with physics and chemical forces, but with the structure of atoms, – remain in an inert state scientific thought can not”.

Key words: biosphere, morphogenesis, paradigm, symmetry.